PEMBUATAN BIODIESEL DARI MINYAK GORENG BEKAS DENGAN PROSES CATALYTIC CRACKING - Buchori, Luqman; Widayat, Widayat (Diponegoro University, 2007)
Crude oil is a source of energy which is not be renewable. This fact motivates so much countries ineconomizing on fuel. Many researches have been done to gets another fuel substitute the crude oil.Biodiesel is represented as fuel instead of diesel fuel, and it is produced from vegetable oil. In the otherside, ex-cooking oil is waste-product from food industry, restaurant and household which is potential tobe alternative fuels because of the high contents of carbon and hydrogen atoms. Commonly the biodieselmade from vegetable oil by esterification and transesterification process. But if using esterification andtransesterification process to ex-cooking oil material, it is not economically feasible because the processmakes another reaction between alkaly catalist and oil to produce soap. One of biodiesel process iscatalytic cracking of the ex-cooking oil. This research is aimed to analyze zeolite catalist size effect(0.125mm; 0.3375mm; 0.425mm; 0.85mm; 1.18mm), and acid concentration on the product (2N; 3N;4N). This result shows that at 4N acid concentration and 0.125 mm zeolite catalist size is optimal whichcan reach diesel specification.